Air temperature variability and trends over Greece - Philandras, C. M.; Nastos, P. T.; Repapis, C. C. (Global Nest Journal, 2008)
In this study, the variability and trends of the mean annual and seasonal surface air temperature in Greek peninsula are examined. The climatic data used, concern mean monthly values of air temperature of 20 meteorological stations of the Hellenic Meteorological Service, for the period 1951-2000. The air temperature time series for each station are analyzed, so that the variability and trends be described. Regarding the annual time series, a cooling trend is observed since the early 1960's till the middle of the decade of 1970, when the trend reverses to heating till nowadays. It is remarkable that the today air temperature levels do not exceed the levels of the middle of the century. During the winter, it is crystal clear that a cooling trend exists from the middle of the decade of 1950 to the end of the decade of 1980, especially in the south region of the country. Afterwards an increasing trend is obvious till nowadays. The pattern in spring appears a slight heating trend in the northern region of Greece and a cooling trend in the south. The summer time series are similar to the annual ones, so the contribution of summer to annual variability is unquestionable. Generally speaking, the air temperature in autumn follows the same distribution in time. In the process, the Factor Analysis is applied on the mean annual and seasonal air temperature and thereafter the regions, within the air temperature covariates, are defined. Finally, the application of spectral analysis to annual and seasonal air temperature is regarded necessary so that the periodicities are derived. © 2008 Global NEST Printed in Greece. All rights reserved.
Keywords: Air temperature trends; Factor analysis; Greece; spectral analysis